Penyelesaian Pinjaman Bermasalah dalam Perusahaan Teknologi Finansial di Indonesia - Randy Pramira Harja; Ekawestri Prajwalita Widiati (Universitas Airlangga, 2021)
Abstract The development of financial technology services has experienced extraordinary growth and can alter as source of fund for the community, especially start-up business or small scale entrepreneur. This development has also followed by negative aspect, namely the growth in the percentage of bad credit or the default rate of loan repayments of more than 90 days (TWP90). This is exacerbated by the absence of a sufficient regulation regarding the settlement of non-performing loans or defaults where this will cause high risk for fin-tech operators and financiers (investors). In fin-tech services, there are 3 legal relationships arise: 1) namely between loan recipients and loan service providers; 2) between service providers and lenders, and 3) between loan recipients and lenders. In addition, the validity of electronic agreements made in fin-tech services does not in conflict with the norms according to article 1320 BW concerning validity of agreement. Legal action that can be taken by fin-tech operators and investors are through litigation or non-litigation procedure respectively mediation, adjudication and arbitration.Keywords: Financial Technology; Fintech; Loans; Debt;Litigation; Non-Litigation.Abstrak Perkembangan layanan teknologi finansial atau yang lebih dikenal dengan financial technology di Indonesia telah mengalami pertumbuhan yang luar biasa dan bisa menjadi alternatif pembiayaan bagi masyarakat khususnya UMKM. Perkembangan ini juga dibarengi aspek negatif yaitu mulai tumbuhnya presentase kredit macet atau tingkat wanprestasi pengembalian pinjaman lebih dari 90 hari (TWP90). Hal ini diperparah belum adanya payung hukum dari regulator terkait penyelesaian pinjaman bermasalah atau gagal bayar dimana hal ini akan menyebabkan resiko yang tinggi bagi penyelenggara tekfin dan pemberi dana (investor). Dalam layanan tekfin terdapat 3 hubungan hukum yang timbul yaitu antara penerima pinjaman dengan penyelenggara layanan pinjaman, antara penyelenggara layanan dengan pemberi pinjaman, dan antara penerima pinjaman dengan pemberi pinjaman. Selain itu keabsahan perjanjian elektronik yang dibuat dalam layanan tekfin tidak bertentangan dengan syarat sah perjanjian menurut pasal 1320 BW. Upaya hukum yang bisa dilakukan oleh penyelenggara tekfin dan investor adalah melalui jalur litigasi atau non litigasi yaitu mediasi, ajudikasi dan arbitrase.Kata Kunci:Tekfin; Pinjaman Bermasalah; Gagal Bayar; Ligitasi; Non Ligitasi.